A Combinatorial Electrochemical Biosensor for Sweat Biomarker Benchmarking. (February 2020) - Ganguly, Antra; Rice, Paul; Lin, Kai-Chun; Muthukumar, Sriram; Prasad, Shalini
Misclassification of an acute disease condition as chronic and vice versa by electrochemical sweat biomarker sensors can cause significant psychological, emotional, and financial stress among patients. To achieve higher accuracy in distinguishing between a chronic condition and an acute condition, there is a need to establish a reference biomarker to index the actual chronic disease biomarker of interest by combinatorial sensing. This work provides the first technological proof of leveraging the chloride ion content in sweat for a combinatorial sweat biomarker benchmarking scheme. In this scheme, the sweat chloride ion has been demonstrated as the reference/indexing biomarker, while sweat cortisol has been studied as the disease biomarker of interest. Label-free affinity biosensing is achieved by using a two-electrode electrochemical system on a flexible substrate suitable for wearable applications. The electrochemical stability of the fabricated electrodes for biosensing applications was studied by open-circuit potential measurements. Attenuated total reflectance–Fourier transform infrared spectroscopy spectra validate the crosslinker–antibody binding chemistry. Concentration-dependent analyte–capture probe binding induces a modulation in the electrical properties (charge transfer resistance and double-layer capacitance) at the electrode–sweat buffer interface, which are transduced by nonfaradaic electrochemical impedance spectroscopy (EIS). Calibration dose responses for the sensor for cortisol (5–200 ng/mL) and chloride (10–100 mM) detection were evaluated in synthetic (pH 6) and pooled human sweat ( R 2  > 0.95). The variation in the cortisol sensor response due to fluctuations in sweat chloride levels and the significance of reporting normalized biomarker levels were demonstrated to further emphasize the need for biomarker benchmarking in electrochemical sensors.